Il viaggio [compact disc] / Melanie de Biasio. - De Biasio, Melanie, 1978-
Il Viaggio was born from an awakened emotional memory. It offers a quest for musical, physical, and spiritual renewal. With a combination of concrete and ambient, this album drifts between the natural sounds of daily life and a dreamlike, imagined world. Melanie decided to retrace the route of her father's parents when immigrating from Italy to Belgium. The focus track 'San Liberatore' is named after the Italian church where their journey started.